TRANSITION FROM THE FREE ENERGY PRINCIPLE (FEP) TO THE INFORMATIONAL SINGULARITY OF SELF-AWARENESS (ISA): ISA AS A MIRROR OF FEP IN CONSCIOUSNESS - Jaued Braga Felício da Silva, Lucas (Revista Gênero e Interdisciplinaridade, 2025)
Karl Friston’s (2006) Free Energy Principle (LEP) provides a comprehensive framework for understanding how biological systems, especially the brain, function to maintain homeostasis and predictability by minimizing uncertainty. However, this approach, while powerful, remains primarily within the domain of biological and computational processes. The Informational Singularity of Self-Awareness (ISA) can be seen as a transition from this approach to a phenomenological perspective, where the intrinsic meaning of these processes for consciousness is considered and explored.